1995
DOI: 10.1002/cne.903550205
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT1A receptor localization on the axon hillock of cervical spinal motoneurons in primates

Abstract: Serotonin (5-HT) has direct and specific effects on the activity of spinal cord motoneurons. The 5-HT1A receptor has been shown to mediate motoneuron responses in spinal reflex pathways using the highly selective 5-HT1A receptor agonist 8-OH-DPAT. We have developed an antipeptide antibody that recognizes a specific region (the second external loop) of the 5-HT1A receptor. This 5-HT1A receptor antibody labels populations of neurons and glia in the primate cervical spinal cord. The highest receptor density is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…It has previously been suggested that cortical py ramidal neurons contain a significant number of 5-HTIA receptors (Francis et al 1992). The 5-HT 1A receptor-IR of the axon hillock has also been reported in the monkey s pinal cord (Kheck et al 1995). The reason for the locali zed concentration of 5-HT 1A rcceptor-IR with the 51A-170 anti peptide antibody is certainly due to the s pecific cpitope selected (aa 170-186).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has previously been suggested that cortical py ramidal neurons contain a significant number of 5-HTIA receptors (Francis et al 1992). The 5-HT 1A receptor-IR of the axon hillock has also been reported in the monkey s pinal cord (Kheck et al 1995). The reason for the locali zed concentration of 5-HT 1A rcceptor-IR with the 51A-170 anti peptide antibody is certainly due to the s pecific cpitope selected (aa 170-186).…”
Section: Discussionmentioning
confidence: 74%
“…'Ci fic pattern of immunoreactivity observed in brain and s pin"l cord sections. The antigen peptide was serially diluted from 750 mg/ mlto 0.075 mg/ ml with affinity pu rified SIA -\ 70 antibody (1/6OCXJ) and mixed for 4 to 6 hours under constant agitation prior to incubation of tissue slices (Kheck et al 1995). No specific sltlining in tissue slices above background labeling was detected with the preimmune serum and a gradual blockade was secn with the serially diluted p reabsorbcd serum (total blocking occurrt""-d at 7.5 mg/ ml).…”
Section: Antibody Preparat Ionmentioning
confidence: 99%
“…function experimentally (Lalley et al, 1994;Sahibzada et al, 2000;Teng et al, 2003) and clinically (Mendelsohn et al, 1991). Although the precise mechanisms are not clear, antibody studies have demonstrated the presence of 5-HT 1A on the axon hillocks of ventral horn motoneurons in the cervical spinal cord of primates (Kheck et al, 1995), possibly indicating a direct stimulatory pathway (Takahashi and Berger, 1990;Richmonds and Hudgel, 1996). Because the greatest density of 5-HT 1A receptors is found in the superficial layers of the dorsal horns of the spinal cord (Thor et al, 1993;Kheck et al, 1995), we also reasoned that 5-HT 1A agonists may, alternatively, act on a pathway involving the afferents from respiratory muscles to supraspinal respiratory centers (Teng et al, 1999).…”
Section: Effect Of C5 Hemicontusion Sci On General Somatic Neurobehavmentioning
confidence: 99%
“…For example, 5-HT receptors could be located near the siz in all but the PD and PY motoneurons. This has been shown for primate motoneurons, for example, in which 5-HT 1A receptors are concentrated at the axon hillock (Kheck et al, 1995). The sizs for stomatogastric neurons are thought to reside in the large diameter processes in the coarse neuropil (Raper, 1979;Miller, 1980).…”
Section: Discussionmentioning
confidence: 90%